2013
DOI: 10.1007/s11207-012-0222-3
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Small Ellerman Bomb Events

Abstract: The properties of Ellerman bombs (EBs), small-scale brightenings in the H-alpha line wings, have proved difficult to establish due to their size being close to the spatial resolution of even the most advanced telescopes. Here, we aim to infer the size and lifetime of EBs using high-resolution data of an emerging active region collected using the Interferometric BIdimensional Spectrometer (IBIS) and Rapid Oscillations of the Solar Atmosphere (ROSA) instruments as well as the Helioseismic and Magnetic Imager (HM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 29 publications
3
45
2
2
Order By: Relevance
“…A skeleton version of this code was adapted to test its functionality in comparison with other existing codes. This resulted in finding a similar amount of EB detections arcsec −2 s −1 as in previous studies (Nelson et al 2013a;Vissers et al 2013). Using the co-aligned spectropolarimetric data from the SST, it was shown that the code produced a higher proportion of strong, bipolar detections when an impulsive criterion was applied.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…A skeleton version of this code was adapted to test its functionality in comparison with other existing codes. This resulted in finding a similar amount of EB detections arcsec −2 s −1 as in previous studies (Nelson et al 2013a;Vissers et al 2013). Using the co-aligned spectropolarimetric data from the SST, it was shown that the code produced a higher proportion of strong, bipolar detections when an impulsive criterion was applied.…”
Section: Discussionsupporting
confidence: 75%
“…The quiet-Sun profile was taken over an area of 200 pixels 2 (11.84″ 2 ), centered about the position X = 43 216, Y = 20 128, seen in the red box of Figure 1. The intensity threshold for the grown area is the same as that of Nelson et al (2013a). The size criterion was added to ensure that no small-scale anomalies were picked up as detections.…”
Section: Eb Detection and Trackingmentioning
confidence: 99%
See 2 more Smart Citations
“…Georgoulis et al( 2002) obtained a higher energy of EBs to be 3×10 28 ergs. However, using a similar value of the net radiative loss rate and taking the height of a EB to be 100 km, Nelson et al ( 2013) estimated the EB energies being in the range of 2 × 10 22 -4 ×10 25 ergs, which is three to four orders of magnitude lower than that in Georgoulis et al( 2002). To elucidate the physical mechanism of EBs, spectral data with high spatial and temporal resolutions are imperative.…”
Section: Introductionmentioning
confidence: 99%